2020
DOI: 10.1016/j.amepre.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

National Prevalence of Sexual Violence by a Workplace-Related Perpetrator

Abstract: Introduction-Workplace sexual violence is not a new phenomenon but has received increased attention recently with the re-emergence of the #metoo movement. Gaps exist in the understanding of the prevalence of this problem in the U.S., its perpetrators, and its impacts. Methods-Using 2010−2012 data from the National Intimate Partner and Sexual Violence Survey (22,590 women and 18,584 men), this study examined the prevalence of several types of sexual violence by a workplace-related perpetrator (authority figure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 21 publications
(24 reference statements)
3
18
0
4
Order By: Relevance
“…The subgroup analysis also indicated that the pooled prevalence of workplace sexual violence among health care professionals was 12% (95% CI 7% to 19%), which is similar to the previous systematic review and meta-analysis [80]. This finding is higher than the workplace sexual violence in America [76] and China [81]. One of the crucial reasons for the study differences might be the difference in the measurement of sexual violence, sociodemographic status, culture, and study methods.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The subgroup analysis also indicated that the pooled prevalence of workplace sexual violence among health care professionals was 12% (95% CI 7% to 19%), which is similar to the previous systematic review and meta-analysis [80]. This finding is higher than the workplace sexual violence in America [76] and China [81]. One of the crucial reasons for the study differences might be the difference in the measurement of sexual violence, sociodemographic status, culture, and study methods.…”
Section: Discussionsupporting
confidence: 82%
“…This systematic review and meta-analysis indicated that the pooled prevalence of workplace sexual violence in Ethiopia was 22% ranging from 17 to 28%. This finding was higher than the prevalence of workplace violence among Korean employees [75] and American employees [76]. However, it was lower than workplace sexual violence among Nigerian employees (63.8%) [77].…”
Section: Discussionmentioning
confidence: 89%
“…26 Sexual abuse was defined as sexual humiliation (forced masturbation or nudity), sexual slavery, rape (vaginal, oral, anal, or attempted), genital abuse (beatings, electric shock, or mutilation), castration, penis amputation, sterilization, or forced marriage, cohabitation, or sexual activity (with a stranger, family member, or corpse). 26 , 27 However, to differentiate between physical and sexual abuse, the respondents were intentionally asked with caution whether the specific event included the sexual organs or not. Because Rohingya women were reluctant to respond to the question of sexual abuse as an individual option, we added the option of both physical and sexual abuse together.…”
Section: Methodsmentioning
confidence: 99%
“…In the United States, 5.6% of women reported sexual violence by a workplace-related perpetrator. 7 In Europe, women exposed to sexual harassment at work in the past 12 months was reported to be highest in Spain (31%) and lowest in UK (17%). 8 In India, the percentage of women acknowledging sexual harassment as per 5 different studies [9][10][11][12][13] ranges from 8%, 15%, 18.75%, 28.8% to 57%, respectively.…”
Section: Introductionmentioning
confidence: 98%